Cardiovascular fingolimod effects on rapid baroreceptor unloading are counterbalanced by baroreflex resetting - Hilz, Max-Josef; Roy, Sankanika; de Rojas Leal, Carmen; Liu, Mao; Canavese, Francesca; Winder, Klemens; Hoesl, Katharina M.; Lee, De Hyung; Linker, Ralf A.; Wang, Ruihao (Neurological Sciences, 2021)
Background and purpose: Initial cardiovascular fingolimod effects might compromise baroreflex responses to rapid blood pressure (BP) changes during common Valsalva-like maneuvers. This study evaluated cardiovascular responses to Valsalva maneuver (VM)-induced baroreceptor unloading and loading upon fingolimod initiation. Patients and methods: Twenty-one patients with relapsing-remitting multiple sclerosis performed VMs before and 0.5, 1, 2, 3, 4, 5, and 6 hours after fingolimod initiation. We recorded heart rate (HR) as RR intervals (RRI), systolic and diastolic BP (BPsys, BPdia) during VM phase 1, VM phase 2 early, VM phase 2 late, and VM phase 4. Using linear regression analysis between decreasing BPsys and RRI values during VM phase 2 early, we determined baroreflex gain (BRG) reflecting vagal withdrawal and sympathetic activation upon baroreceptor unloading. To assess cardiovagal activation upon baroreceptor loading, we calculated Valsalva ratios (VR) between maximal and minimal RRIs after strain release. Analysis of variance or Friedman tests with post hoc analysis compared corresponding parameters at the eight time points (significance: p < 0.05). Results: RRIs at VM phase 1, VM phase 2 early, and VM phase 2 late were higher after than before fingolimod initiation, and maximal after 4 hours. Fingolimod did not affect the longest RRIs upon strain release, but after 3, 5, and 6 hours lowered the highest BPsys values during overshoot and all BPdia values, and thus reduced VRs. BRG was slightly higher after 3 and 5 hours, and significantly higher after 4 hours than before fingolimod initiation. Conclusions: VR-decreases 3–6 hours after fingolimod initiation are physiologic results of fingolimod-associated attenuations of BP and HR increases at the end of strain and do not suggest impaired cardiovagal activation upon baroreceptor loading. Stable and at the time of HR nadir significantly increased BRGs indicate improved responses to baroreceptor unloading. Thus, cardiovascular fingolimod effects do not impair autonomic responses to sudden baroreceptor loading or unloading but seem to be mitigated by baroreflex resetting.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Baroreflex gain; Baroreflex resetting; Cardiovascular fingolimod effects; Multiple sclerosis; Valsalva maneuver

German Validation of the Composite Autonomic Symptom Score 31 - Wang, Ruihao; Canavese, Francesca; Intravooth, Tassanai; Singer, Wolfgang; Hilz, Max-Josef (NEUROLOGY, 2019)
CRIS-Team WoS Importer:2019-08-02

Pre-existing parasympathetic dominance seems to cause persistent heart rate slowing after 6 months of fingolimod treatment in patients with multiple sclerosis - Hilz, Max-Josef; Canavese, Francesca; de Rojas Leal, Carmen; Lee, De Hyung; Linker, Ralf A.; Wang, Ruihao (Clinical Autonomic Research, 2024)
Purpose: Vagomimetic fingolimod effects cause heart rate (HR) slowing upon treatment initiation but wear off with sphingosine-1-phosphate receptor downregulation. Yet, prolonged HR slowing may persist after months of fingolimod treatment. We evaluated whether cardiovascular autonomic modulation differs before and 6 months after fingolimod initiation between patients with RRMS with and without initially prolonged HR slowing upon fingolimod initiation. Methods: In 34 patients with RRMS, we monitored RR intervals (RRI) and blood pressure (BP), at rest and upon standing up before fingolimod initiation. Six hours and 6 months after fingolimod initiation, we repeated recordings at rest. At the three time points, we calculated autonomic parameters, including RRI standard deviation (RRI-SD), RRI-total-powers, RMSSD, RRI high-frequency [HF] powers, RRI and BP low-frequency (LF) powers, and baroreflex sensitivity (BRS). Between and among patients with and without prolonged HR slowing upon fingolimod initiation, we compared all parameters assessed at the three time points (analysis of variance [ANOVA] with post hoc testing; significance: p < 0.05). Results: Six hours after fingolimod initiation, all patients had decreased HRs but increased RRIs, RRI-SDs, RMSSDs, RRI-HF-powers, RRI-total-powers, and BRS; 11 patients had prolonged HR slowing. Before fingolimod initiation, these 11 patients did not decrease parasympathetic RMSSDs and RRI-HF-powers upon standing up. After 6 months, all parameters had reapproached pretreatment values but the 11 patients with prolonged HR slowing had lower HRs while the other 23 patients had lower parasympathetic RMSSDs and RRI-HF-powers, and BRS than before fingolimod initiation. Conclusion: Our patients with prolonged HR slowing upon fingolimod initiation could not downregulate cardiovagal modulation upon standing up even before fingolimod initiation, and 6 months after fingolimod initiation still had more parasympathetic effect on HR while cardiovagal modulation and BRS were attenuated in the other 23 patients. Pre-existing parasympathetic predominance may cause prolonged HR slowing upon fingolimod initiation.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Active standing; Fingolimod; Heart rate slowing; Parasympathetic predominance; Relapsing–remitting multiple sclerosis; Sphingosine-1-phosphate receptor